2017
DOI: 10.1016/j.bbmt.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Cell Transplantation–Specific Comorbidity Index Predicts Morbidity and Mortality in Autologous Stem Cell Transplantation

Abstract: The hematopoietic cell transplantation-specific comorbidity index (HCT-CI) score is a useful tool to assess the risk for nonrelapse mortality (NRM) after allogeneic hematopoietic stem cell transplantation. Although the HCT-CI has been investigated in autologous stem cell transplantation (ASCT), its use is limited. To improve on the current use of the HCT-CI score on the morbidity and mortality after ASCT, we assessed the 100-day morbidity defined as orotracheal intubation (OTI), dialysis or shock (vasopressors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…18 Additionally, some other study groups reported similar results, and one group even identified the BeEAM regimen being an independent risk factor for non-relapse mortality. [19][20][21] We observed in our 41 patients only a transient and not clinical relevant elevation in creatinine levels in the days following bendamustine. No therapeutic intervention was necessary due to renal toxicity.…”
Section: Responsementioning
confidence: 47%
See 1 more Smart Citation
“…18 Additionally, some other study groups reported similar results, and one group even identified the BeEAM regimen being an independent risk factor for non-relapse mortality. [19][20][21] We observed in our 41 patients only a transient and not clinical relevant elevation in creatinine levels in the days following bendamustine. No therapeutic intervention was necessary due to renal toxicity.…”
Section: Responsementioning
confidence: 47%
“…Interestingly, in a retrospective analysis, they observed an increased renal toxicity in 28% of patients, including 4 patients with grades 3 and 4 side effects and one case of dialysis . Additionally, some other study groups reported similar results, and one group even identified the BeEAM regimen being an independent risk factor for non‐relapse mortality …”
Section: Discussionmentioning
confidence: 82%
“…In addition to R-ISS, HCT-CI > 2, receipt of >1 line of pre-AHCT chemotherapy, and year of AHCT 2008 to 2011 (compared with 2012 to 2014) were associated with worse OS in this cohort. HCT-CI and lines of treatment have been shown to be associated with OS in MM in multiple studies [18][19][20]. Similarly, receipt of more than 1 line of therapy before AHCT has not shown to be of benefit even among patients who achieve suboptimal response to first line of treatment [21].…”
Section: Discussionmentioning
confidence: 99%
“…The HCT‐CI is a tool designed to predict post‐HCT outcomes based on the collective influence of a number of pretransplant comorbidities. The comorbidity index is widely used for the assessment of the risk of NRM in both allogeneic and more recently autologous HCT . The purpose of the present retrospective study was to investigate the influence of the individual pretransplant parameters of the HCT‐CI on the outcomes of AML patients that underwent allogeneic HCT.…”
Section: Discussionmentioning
confidence: 99%
“…The comorbidity index is widely used for the assessment of the risk of NRM in both allogeneic and more recently autologous HCT. 20,21 The purpose of the present retrospective study was to investigate the influence of the individual pretransplant parameters of the HCT-CI on the outcomes of AML patients that underwent allogeneic HCT. The HCT-CI overall demonstrated prognostic stratification for OS in our cohort; however, a significant difference was not observed between the lower scores (0 vs 1-2).…”
Section: Discussionmentioning
confidence: 99%